An approach for efficient ship routing - Romero, Gonzalo (2013)
Ship routing problems are a particular kind of routing problems, where the vehicles to be routed are vessels or ships, usually in maritime environments. In contrast to land routing, ship routing has unique features, including overnight trips, disjoint time windows, not necessarily pre-specified routes, and a great uncertainty derived from weather conditions. In this work we present a special ship routing problem, which incorporates many features present in general ship routing settings. We discuss aspects related with data gathering and updating, which are particularly difficult in the context of ship routing. Additionally, we present a GRASP algorithm to solve this problem. We apply our solution approach to a salmon feed supplier based in southern Chile, and present computational results on real data.